2015
DOI: 10.3109/13880209.2014.1001406
|View full text |Cite
|
Sign up to set email alerts
|

Leonurine hydrochloride induces apoptosis of H292 lung cancer cell by a mitochondria-dependent pathway

Abstract: (2015) Leonurine hydrochloride induces apoptosis of H292 lung cancer cell by a mitochondria-dependent pathway, Pharmaceutical Biology, 53:11, 1684-1690, DOI: 10.3109/13880209.2014 Objective: This study investigated its effects on human non-small cell lung cancer (NSCLC) H292 cells and illustrated the possible mechanism involved. Materials and methods: After treatment with different concentrations of LH (0, 10, 25, and 50 mmol/L) for 6, 12, 24, 48, and 72 h, the cell viability was assessed by the MTT assay. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…It has been previously demonstrated than Bax/Bcl-2 protein are associated with apoptosis ( 17 , 18 ). In order to further demonstrate the effect of RGZ on apoptosis, the expression of Bax and Bcl-2 was examined by western blotting in RGZ-treated HepG2 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously demonstrated than Bax/Bcl-2 protein are associated with apoptosis ( 17 , 18 ). In order to further demonstrate the effect of RGZ on apoptosis, the expression of Bax and Bcl-2 was examined by western blotting in RGZ-treated HepG2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Caspase 3 activation has previously been demonstrated to serve an important role in apoptosis ( 17 , 18 ). The present results demonstrated that administration of RGZ can significantly reduce levels of caspase 3 (P<0.001 and P<0.05 compared with the control and GW9662-treated cells, respectively) and increase cleavage-caspase 3 (P<0.001 compared with the which further indicated that RGZ could induce the apoptosis of HepG2 cells (P<0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Although some plants of the genus Artemesia are known to be toxic, Artemisia princeps is a commonly used herb in traditional medicines, teas, and as a cooked green vegetable. It is rich in a variety of nutrients and is generally considered to a safe food [ 37 ]. Leonurus japonicas is a very commonly used herb in Oriental Medicine with a well-established record for safe use; one of its valuable properties is as a hepatoprotective intervention against liver toxins [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these herbs have not been reported to have side effects and toxicity and they are registered as foods by the Korean Food and Drug Administration. However, since they have been demonstrated to cause apoptosis of carcinoma cells [ 37 , 38 ], they might have some toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Anticancer drugs from Chinese medicine have attracted the interest of researchers in the past decades [9].…”
Section: Introductionmentioning
confidence: 99%